2017
DOI: 10.1016/j.chroma.2017.01.078
|View full text |Cite
|
Sign up to set email alerts
|

A cyclic-olefin-copolymer microfluidic immobilized-enzyme reactor for rapid digestion of proteins from dried blood spots

Abstract: A critical step in the bottom-up characterization of proteomes is the conversion of proteins to peptides, by means of endoprotease digestion. Nowadays this method typically uses overnight digestion and as such represents a considerable bottleneck for high-throughput analysis. This report describes protein digestion using an immobilized-enzyme reactor (IMER), which enables accelerated digestion times that are completed within seconds to minutes. For rapid digestion to occur, a cyclic-olefin-copolymer microfluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Hydrodynamic chromatography analysis indicated that the particles had an average size of 130 nm (see Supplementary Material, section S-2 for the corresponding data). Based on previous information we expect the diameter of the through pores of the IMER-containing monoliths to be in the range of 0.8e1.5 mm [18]. For recording the calibration curves, 5000 ppm solutions of all standards were individually prepared in unstabilized THF and diluted to 1000 ppm, also in unstabilized THF, for analysis (see Supplementary Material, section S-3 for the calibration curves).…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrodynamic chromatography analysis indicated that the particles had an average size of 130 nm (see Supplementary Material, section S-2 for the corresponding data). Based on previous information we expect the diameter of the through pores of the IMER-containing monoliths to be in the range of 0.8e1.5 mm [18]. For recording the calibration curves, 5000 ppm solutions of all standards were individually prepared in unstabilized THF and diluted to 1000 ppm, also in unstabilized THF, for analysis (see Supplementary Material, section S-3 for the calibration curves).…”
Section: Sample Preparationmentioning
confidence: 99%
“…The procedure to immobilize enzymes in-situ in the microfluidic channels was adapted from the method described elsewhere [18], and consisted of three major steps: i) surface modification of the cyclic-olefin copolymer microchannel and in-situ polymerization of the polymer monolith, ii) photografting of poly(ethylene glycol) methacrylate and 2-vinyl-4,4-dimethylazlactone, and iii) lipase immobilization. During the last step, a 2000 mg/L aqueous solution of lipase containing NaCl (0.9% by weight) was pumped through the microdevice for 2 h at 0.5 mL min À1 .…”
Section: Enzyme-immobilization Processmentioning
confidence: 99%
See 1 more Smart Citation
“…To cope with the increasing numbers of samples and to implement the technique in a QC environment with HRAM LC-MS, sample preparation reproducibility is also required which can be provided by automation through online digestion or robotic systems [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme immobilization on solid supports has fueled advances in biosensing, 1,2 biocatalysis, 3 and proteomics, 4,5 among other fields. The history, applications, and available methods of enzyme immobilization are vast, as covered in various reviews.…”
mentioning
confidence: 99%